Robotic radiosurgery system patient‐specific QA for extracranial treatments using the planar ion chamber array and the cylindrical diode array. (8th July 2015) - Lin, Mu‐Han; Veltchev, Iavor; Koren, Sion; Ma, Charlie; Li, Jinsgeng
Abstract : Robotic radiosurgery system has been increasingly employed for extracranial treatments. This work is aimed to study the feasibility of a cylindrical diode array and a planar ion chamber array for patient‐specific QA with this robotic radiosurgery system and compare their performance. Fiducial markers were implanted in both systems to enable image‐based setup. An in‐house program was developed to postprocess the movie file of the measurements and apply the beam‐by‐beam angular corrections for both systems. The impact of noncoplanar delivery was then assessed by evaluating the angles created by the incident beams with respect to the two detector arrangements and cross‐comparing the planned dose distribution to the measured ones with/without the angular corrections. The sensitivity of detecting the translational (1–3 mm) and the rotational (1°–3°) delivery errors were also evaluated for both systems. Six extracranial patient plans (PTV 7–137 cm 3) were measured with these two systems and compared with the calculated doses. The plan dose distributions were calculated with ray‐tracing and the Monte Carlo (MC) method, respectively. With 0.8 by 0.8 mm 2 diodes, the output factors measured with the cylindrical diode array agree better with the commissioning data. The maximum angular correction for a given beam is 8.2% for the planar ion chamber array and 2.4% for the cylindrical diode array. The two systems demonstrate a comparable sensitivity of detecting the translational targeting errors, while the cylindrical diode array is more sensitive to the rotational targeting error. The MC method is necessary for dose calculations in the cylindrical diode array phantom because the ray‐tracing algorithm fails to handle the high‐Z diodes and the acrylic phantom. For all the patient plans, the cylindrical diode array/ planar ion chamber array demonstrate 100 % / > ; 92 % ( 3 % / 3 mm ) passing rates. The feasibility of using both systems for robotic radiosurgery system patient‐specific QA has been demonstrated. For gamma evaluation, 2 % / 2 mm criteria for cylindrical diode array and 3 % / 3 mm criteria for planar ion chamber array are suggested. The customized angular correction is necessary as proven by the improved passing rate, especially with the planar ion chamber array system. PACS number: 29.40.‐n